Emily windsnap : A Tangle of Tails - Kessler, Liz; Gibb, Sarah (Somerville, Massachusetts : Candlewick Press, 2014)
The tail of Emily Windsnap: After finally convincing her mother that she should take swimming lessons, twelve-year-old Emily discovers a terrible and wonderful secret about herself that opens up a whole new world.
Emily Windsnap and the monster from the deep: Reunited with her merman father and now living on an island located in the Bermuda Triangle, twelve-year-old Emily accidentally awakens the fearsome kraken and also faces a bully from her past.
The tail of Emily Windsnap -- Emily Windsnap and the monster from the deep.
The tail of Emily Windsnap -- Emily Windsnap and the monster from the deep.
Ages 8-12.
Keywords: Windsnap, Emily (Fictitious character) -- Juvenile fiction; Mermaids -- Juvenile fiction; Swimming -- Juvenile fiction; Friendship -- Juvenile fiction